Substance abuse as a cause of violence in persons diagnosed with schizophrenia - Dimitrijević Aleksandar; Živković Anja; Božović Maša (Temida)
Persons diagnosed with schizophrenia can both inflict and suffer violence. For centuries there has been a firmly held belief that they are dangerous and, due to this belief, they are still frequently isolated from the community and exposed to involuntary treatment and restraint. Research data illustrates that persons with this diagnosis are at greater risk of performing violent acts more frequently than the general population. In recent years, the general framework has been set in a more complex manner due to the inclusion in analysis of several mediating variables such as gender, social status, childhood trauma, personality traits, stress and many others. Numerous studies have shown that violent tendencies are evident in persons with co-morbidity of schizophrenia and anti- social personality disorder and/or substance abuse disorders. This paper is focused on reviewing data scrutinizing the role of drug abuse and alcoholism in the violent behavior of persons diagnosed with schizophrenia. Data obtained through meta- analyses of tens of thousands of cases demonstrates unequivocally that the percentage of persons with schizophrenia who commit violent acts without abusing drugs is relatively higher than in the general population (8.5% : 5.3%), while persons who abuse drugs and/or alcohol have been more frequently violent regardless of being psychotic or not (27.6%). Having taken these findings into account, the understanding that persons diagnosed with schizophrenia are prone to violence must be made more specific and their treatment, follow- up and public image changed accordingly. Some of these implications are discussed in this paper and changes suggested.